BEBERAPA FAKTOR YANG MEMPENGARUHI KEBIJAKAN UTANG : Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Nurcholis, Mafvaza Fitria; Triyani, Yustina (Jurnal Akuntansi, 2024)
Leverage is an alternative source of financing from outside the company which can offer advantages and disadvantages for the company. The purpose of This research is to analyze the impact of independent variables such as profitability, fixed tangible assets, liquidity, company size, and opportunities growth on company leverage. Trade-off theory is used in research. This is to explain the condition of the company's overall capital structure using debt. Profitability is the ability of a company to do to generate profits over a certain period at the level of sales, assets, and share capital certain. Tangible fixed assets are tangible assets with a useful life of more than one year. Liquidity is the degree to which an asset can be easily converted into money. Company size is a way to group the scale of a company seen from the size of the company. Growth opportunity is an opportunity future growth of a company. This research will use manufacturing companies that have been registered on the BEI (Indonesian Stock Exchange) for the 2019 period 2021 as an object. Based on the t test, the Sig value is obtained. for X1: 0.285, X2: 0.077, X3: 0.000, X4: 0.064, X5: 0.002. The coefficient results from the t test show the value of X1: 0.097, X2: 0.210, X3: -0.184, X4: -0.006, X5: 0.270. Results of the coefficient of determination for the research model shows a value of 0.501. The conclusions obtained in this research are it is not proven that profitability, tangible fixed assets, and company size have influence on leverage. There is evidence that liquidity has a negative effect on leverage and growth opportunities have a positive effect on leverage.